Effect of Farmers-Herders Conflict on School Enrollment in Benue State - Adeyi, Ngbede; Adamu, Mahmud Ibrahim; Itodo, Sylvanus Mohammed (Kashere Journal of Politics and International Relations, 2024)
This study analyzed the effect of farmers-herders conflict on the school enrollment in Benue state. The study sought to achieve the following objectives: analyzing the temporal variations in school enrollment rates in Benue State due to the farmers-herders conflict; assessing the influence of the farmers-herders conflict on the quality of education in schools located in conflict-affected areas of Benue State; and examining the impact of the farmers-herders conflict on student participation rates in schools within Benue State. The study adopted both the survey and documentary design as its method for the collection of data. The population of the study consisted of the 692,000 indigenes of Agatu, Guma and Logo Local Government Area of Benue State. The findings of the study revealed that the farmers-herders conflict in Benue State has had a significant impact on school enrollment rates, indicating a noticeable fluctuations in enrollment rates over time due to the conflict. The study also revealed that the farmers-herders conflict in Benue State has had a significant negative impact on the quality of education in schools located in conflict-affected areas. The study therefore recommended that the policymakers, educators, and stakeholders should prioritize targeted interventions to mitigate the disruptive effects of the farmers-herders conflict on school enrollment rates in Benue State. Also, policymakers and education authorities should prioritize comprehensive measures to address the adverse effects of the farmers-herders conflict on the quality of education in conflict-affected areas of Benue State